Value-Based Cadre Development in a Faith-Based Student Organization: The KSATRIA Program at UIN Sunan Kalijaga Yogyakarta - Lutfi Nugraha Putra Pambayun; Nora Saiva Jannana; Heru Sulistya (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2026)
This study examines the role of the ASWAJA Santri Cadre Program (KSATRIA) in developing the intellectual, spiritual, and social competencies of KMNU UIN Sunan Kalijaga members. A qualitative design was applied involving 15 participants, comprising three administrators, eight active cadres, and four alumni. Data were collected through semi-structured interviews, participatory observation, and document analysis and were analyzed using data condensation, data display, and conclusion drawing. The findings show that KSATRIA operates through recruitment, orientation, core training, practical activities, and evaluation. Its integration of ASWAJA, ke-NU-an, organizational learning, leadership simulation, and community service supports ideological understanding, analytical ability, spiritual value internalization, teamwork, communication, and organizational participation. The program also strengthens the application of tasamuh, tawazun, i‘tidal, and rahmatan lil ‘alamin in organizational practice. However, implementation is constrained by differences in participant motivation, limited resources, academic schedules, and resistance to participatory and technology-supported methods. The study demonstrates that value-based cadre development can integrate human capability formation, organizational commitment, and cultural continuity. Its conclusions remain context-specific because the research involved one organization and lacked comparative or longitudinal assessment. Future studies should use multisite, longitudinal, and mixed-method designs.